Indonesia Poros Maritim Dunia (Analisis Teks Media dengan Pendekatan Mix-Methode) - Jamalullail Jamalullail; Husen Mony (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2022)
Mass media is needed for the process of disseminating various messages and discourses regarding the realization of the vision of the World Maritime Axis to the public. The purpose of this study was to determine the frame of the national media coverage and the widely quoted news sources related to Indonesia's policies on the World Maritime Axis. This study uses the theory of the mass media news production process, namely Agenda Setting and Gatekeeping. The method uses a mixed approach at the level of data collection and analysis. The object of research is online media news on November 13, 2014, when President Jokowi announced the vision, until October 20, 2019, when the reign of Joko Widodo – Jusuf Kalla ended. The results showed that national online media coverage of Indonesia's vision as the World Maritime Axis stands at 3,344 articles on average for each media, with 10 issues in it. In general, the national online media coverage of Indonesia's vision as the World Maritime Axis is in a positive frame. For the ten issues studied, most of the media present their coverage in a positive light. Speak persons in news related to the issue of the World Maritime Axis are divided into two, namely: institutionally and personally. Institutionally, the Coordinating Ministry for Maritime Affairs and Investment received the most quotes from the media, followed by the Ministry of Transportation and the Ministry of Marine Affairs and Fisheries. Meanwhile, personally, the Minister of Maritime Affairs and Fisheries, Susi Pudjiastuti, said that her statement was widely covered by the media.